PENGARUH MOTIVASI, LINGKUNGAN KERJA FISIK, DISIPLIN KERJA, DAN PELATIHAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA PERUSAHAAN UMUM DAERAH AIR MINUM TIRTA WIJAYA KABUPATEN CILACAP - Mutiasari Mutiasari; Herni Utami Rahmawati; Suseno Suseno (AmaNU: Jurnal Manajemen dan Ekonomi, 2021)
The research objective was to analyze the influence of motivation, physical work environment, work discipline, and training on employee work productivity at the Tirta Wijaya Regional Public Company, Cilacap Regency. The hypothesis proposed is that motivation, physical work environment, work discipline, and training have an influence on employee work productivity at the Tirta Wijaya Regional Public Drinking Water Company, Cilacap Regency. The type of research is survey method and data were collected based on quistionnaires. The population of this study was 200 people and sample 67 people. The analytical tool used is regression analysis and parcial test (t test). The result showed motivation, physical work environment, work discipline, and training have a significant effect on employee work productivity with the values of t count which bigger than t table. Tirta Wijaya Regional Public Drinking Water Company, Cilacap Regency should make efforts to increase employee productivity by increasing motivation, physical work environment, work discipline, and training.